Microstructure, hardness and wear rate of heat treated Titanium surface alloyed AISI 304 stainless steel. (2018) - Krishna Kumar, M.; Saravanan, R.; Sellamuthu, R.; Narayanan, Vijay
Abstract: AISI 304 stainless steel bar and commercially pure titanium were chosen as the substrate and the alloying material, respectively. The surface alloying process was done using heat generated by the gas tungsten arc source. The surface alloying AISI 304 stainless steel specimens were heat treated in the furnace for 6 h. The intermetallic compound precipitates were observed in the surface alloyed layer. The elemental analysis were observed using the EDS analysis. There was an increase in hardness and decrease in the wear rate on the surface alloyed layer after the heat treatment process.